PENILAIAN RESIKO OPERASIONAL PELAYANAN BONGKAR MUAT KAPAL DI PELABUHAN DILI, TIMOR-LESTE - Minto Basuki; Putu Andhi Indira Kusuma; Zeca Soares (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Dili port is the one of port in Timor Leste, that can be used as loading and unloading of goods. The increasing of operations in recent years was could be to the risk. The aim of this study was to analyze the risks involved in the operations of ships loading and unloading in port of Dili. This study was identifying risks, determine risk level, and risk mitigate that affect the processes of loading and unloading. Samples data were the activities loading and unloading that cause risks or accidents reported in 2010 to 2014. The data were analyzed using risk matrix method at probability (likelihood) and impact (consequence) based on AS/NZS 2004 standard. Using this method, there were 22 risk events do to identified . Using the risk matrix, injured due to exposure to the goods or sharp tools, which include a very high risk rating. This mitigate is to provide safety and health training and use to PPE (Personal Protective Equipment) to the labors.